2017
DOI: 10.4172/2157-7439.s8-003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Stability Studies on Vegetable Nanoemulsions Obtained by Low Energy Process

Abstract: Background: The use of vegetable oils in the pharmaceutical and cosmetic industry is becoming increasingly attractive worldwide. Native to Cerrado biome of Brazil, we can mention baru seeds, which oil has a high degree of unsaturation. Its major constituents are the fatty acids oleic and linoleic, and, besides that it contains significant amounts of tocopherols and phytosterols. Emulsified systems are the most common form presentation of industrial products. Its excellent ability to solubilize hydrophilic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The baru oil, which is rich in unsaturated fatty acids (Siqueira et al, 2016) and was used as the oil phase in the systems, presented an HLB of 7.0. In the HLB determination using TW and SP, this value presented the best droplet size, morphology, and creaminess, agreeing with Maruno (2017) and Moraes et al (2018), who found similar values (6.0-7.0).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The baru oil, which is rich in unsaturated fatty acids (Siqueira et al, 2016) and was used as the oil phase in the systems, presented an HLB of 7.0. In the HLB determination using TW and SP, this value presented the best droplet size, morphology, and creaminess, agreeing with Maruno (2017) and Moraes et al (2018), who found similar values (6.0-7.0).…”
Section: Discussionsupporting
confidence: 78%
“…The size of less than 200 nm and low PDI (0.3) of the formulations globules is characteristic of monodisperse systems and indicated that the systems presented homogeneity, while the incorporation of the extract positively favored the globule diameter in the NBPE since it presented lower values than the NC, which may be associated with its greater solubility in the phases of the system (Islam et al, 2016). Lower values were obtained by Maruno (2017) in nanoemulsions with baru oil, but the percentage of oil phase was lower (10%), in addition to a higher proportion of surfactants and use of co-surfactants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same structure causes good interaction between oil and surfactant so the surfactant can fully cover the surface of oil droplets, resulting excellent physical stability [24]. The use of PMO and PDO as nonionic surfactant associate with amphiphilic polymers which can form viscoelastic interfacial film at oil/water interface to prevent Ostwald ripening destabilization phenomenon [25]. The high surfactant concentration also increased the interfacial area between water phase and oil phase which yielded smaller droplet [26].…”
Section: Oil/surfactant Ratio Effect On Nanoemulsion Particle Size Stmentioning
confidence: 99%